ANALISIS DISIPLIN KERJA KARYAWAN PADA PT TRANS REKREASINDO GRAHA BINTARO - Zaky Yahya, Muhammad; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
This study aims to determine the implementation of employee work discipline at PT Trans Rekreasindo Graha Bintaro and to find out the form of SWOT in carrying out employee work discipline at PT Trans Rekreasindo Graha Bintaro. This study uses a descriptive qualitative approach. Data collection techniques used in this study were observation, interviews, documentation and triangulation. In addition, this study used SWOT data analysis to analyze the company's strengths, weaknesses, opportunities and threats. The results of the study are: having strict sanctions and punishments, the addition of jobdesks beyond the responsibility of the position held, company conditions that provide opportunities for career paths, and differences in working hours among employees.